2009
DOI: 10.1016/j.jfms.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet on glucose control in cats with diabetes mellitus treated with twice daily insulin glargine

Abstract: The purpose of this study was to evaluate the effects of dietary modification in addition to twice daily insulin glargine. Cats were treated with insulin glargine twice daily and randomized to receive either a low carbohydrate, high protein (LCHP) diet (n=6) or a control diet (n=6) for 10 weeks. Re-evaluations of clinical signs, blood glucose curves, and serum fructosamine concentrations were performed at weeks 1, 2, 4, 6, and 10. Two of 12 cats achieved complete remission by the end of the study but remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Low-carbohydrate diets may also contribute to good glycemic control and possible diabetic remission, although data are slim. One study found that remission rate was higher in cats fed a low-carbohydrate diet compared to a moderate carbohydrate diet, whereas in another study, remission rates were similar (Bennet et al, 2006;Hall et al, 2009). However, as mentioned earlier, the studies are difficult to compare because diet composition, type of insulin, and treatment protocols differed.…”
Section: Remission Of Diabetes In Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-carbohydrate diets may also contribute to good glycemic control and possible diabetic remission, although data are slim. One study found that remission rate was higher in cats fed a low-carbohydrate diet compared to a moderate carbohydrate diet, whereas in another study, remission rates were similar (Bennet et al, 2006;Hall et al, 2009). However, as mentioned earlier, the studies are difficult to compare because diet composition, type of insulin, and treatment protocols differed.…”
Section: Remission Of Diabetes In Catsmentioning
confidence: 99%
“…The currently available studies, which have included information on remission, are difficult to compare, because they differ with regard to definition of remission, inclusion criteria of cats, blood glucose targets, and monitoring protocols, as well as type of insulin and type of diet. Published remission rates vary between 13% and 100% (Nelson et al, 1999;Bennett et al, 2006;Martin and Rand, 2007;Boari et al, 2008;Michiels et al, 2008;Marshall et al, 2009;Roomp and Rand, 2009;Hall et al, 2009;Zini et al, 2010;Hafner et al, 2011;Tschuor et al, 2011). It has been suggested that remission rates are higher in cats when treated with newer types of insulin (e.g., insulin analogues such as glargine or detemir) than with other/older types of insulin (e.g., Lente type) (Marshall et al, 2009;Roomp and Rand, 2009;.…”
Section: Remission Of Diabetes In Catsmentioning
confidence: 99%
“…It is further supported by the two previous reports of 27/32 cats and 8/8 cats achieving remission when managed using a regimen similar to our near glycemic paradigm (Marshall et al 2009). When management strategies with a less aggressive target blood glucose ranges than the NEP were used, reported remission rates for cats with DM were lower, ranging from 17% to 50% (Frank et al 2001;Weaver et al 2006;Boari et al 2008;Sieber-Ruckstuhl et al 2008;Hall et al 2009;Zini et al 2010). Likewise, only 14% of the cats managed using TP in our study achieved remission.…”
Section: Discussionmentioning
confidence: 55%
“…Based on a limited body of information the final optimal dose of the control of canine DM ranges between 0.1 and 1.1 U kg -1 but it is typically around 0.5-0.6 U kg -1 (Fracassi et al, 2012;Hess and Drobatz, 2013). For cats with DM insulin glargine treatment is started at 0.25-0.5 U kg -1 BID (the upper end of the dosing regimen is used when blood glucose concentration exceeds 360 mg dl -1 ) or at 1-2 U per cat BID depending on the ideal body weight (1 U if ≤4 kg and 1.5-2 U if >4 kg) (Cook, 2007;Rios and Ward, 2008;Hall et al, 2009;Marshall et al, 2009;Tschuor et al, 2011). Some investigators advocate to adjust the initial dose by hospitalizing cats and performing serial J HELLENIC , 67(2) ΠΕΚΕ 2016 liver penetration (Gilor et al, 2010;Sako et al, 2011; which is also very stable and can be used for up to 6 weeks after opening if kept at room temperature and up to 6 months if refrigerated .…”
Section: Types Of Insulin For Dogs and Cats With Non-complicated Diabmentioning
confidence: 99%